2020
DOI: 10.3389/frph.2020.566559
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Semen Exposure on the Immune and Microbial Environments of the Female Genital Tract

Abstract: Background: Semen induces an immune response at the female genital tract (FGT) to promote conception. It is also the primary vector for HIV transmission to women during condomless sex. Since genital inflammation and immune activation increase HIV susceptibility in women, semen-induced alterations at the FGT may have implications for HIV risk. Here we investigated the impact of semen exposure, as measured by self-reported condom use and Y-chromosome DNA (YcDNA) detection, on biomarkers of female geni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 81 publications
1
19
0
Order By: Relevance
“…We enrolled 152 HIV‐negative women between 20 and 44 years of age from KwaZulu‐Natal who participated in the CAPRISA 008 study [23‐25]. Women participated in the CAPRISA 008 study over two years, between November 2012 and October 2014, and were followed up for an average of 22 months [23,25].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We enrolled 152 HIV‐negative women between 20 and 44 years of age from KwaZulu‐Natal who participated in the CAPRISA 008 study [23‐25]. Women participated in the CAPRISA 008 study over two years, between November 2012 and October 2014, and were followed up for an average of 22 months [23,25].…”
Section: Methodsmentioning
confidence: 99%
“…Women participated in the CAPRISA 008 study over two years, between November 2012 and October 2014, and were followed up for an average of 22 months [23,25]. Demographic data were assessed at baseline, and vaginal specimens (including cervicovaginal lavage (CVL), cytobrushes and vulvovaginal swabs) were collected at enrolment and biannually at months 6, 12, 18, 24 and study exit (average 5 ± 1 visit; 651 genital specimens) as previously reported [24‐27]. Semen biomarkers were measured in vaginal specimens collected at each of the multiple study visits per participant.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the impact that unprotected sexual intercourse has on the vaginal immune response and microbiome, an objective assessment of semen exposure is needed to accurately interpret mucosal immunity and BV data from vaginal fluids of women enrolled in HIV prevention trials. Measurement of semen exposure using biomarkers has been identified as a robust method to reduce the reliance on self-reported sexual activity in studies investigating immunological factors in the FGT, risk of infection or probability of pregnancy (22)(23)(24)(25)(26). Two semen biomarkers; prostate-specific antigen (PSA) and the Ychromosome DNA, have been used to indicate the presence of semen within the FGT (27,28).…”
Section: Introductionmentioning
confidence: 99%
“…Several factors in semen may also inhibit the activity of extracellular H 2 O 2 produced by Lactobacilli species and thus promote the growth of BV‐associated microbes 195 . We have demonstrated that recent semen exposure is associated with increased detection of BVAB‐2, Prevotella bivia , and G. vaginalis and reduced detection of Lactobacillus jensenii in vaginal specimens (Jewanraj et al, 2021; accepted) 165 . Increases in other gut‐associated microbes have also been observed in the FGT after protected sexual intercourse, suggesting that these alterations in the vaginal microbiota may also be associated with mechanical contamination rather than just semen itself 185,187 .…”
Section: Contributions Of Semen To Female Genital Inflammationmentioning
confidence: 96%